PENGARUH JUMLAH WAJIB PAJAK BADAN, PEMERIKSAAN PAJAK, TINGKAT KEPATUHAN WAJIB PAJAK BADAN TERHADAP PENERIMAAN PAJAK PENGHASILAN DI KPP PRATAMA TAMBORA - MIRANDA TURUSAKA SAU (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Directorate General of Taxation difficulties to achieve the target of tax revenue. A number of attempts were made. Through extra efforts, DJP will explore the potential tax revenue. According to Darmin Nasution, to raise the tax rate, the only way is with intensification and extensification. Factors that represent extensification and intensification are the number of taxpayers, number of tax inspection and taxpayer compliance level.The research aimed to find out whether the revenue of income tax at Tambora Tax Office Service influenced by the number of Corporation Taxpayers, number of tax inspection, and Taxpayer compliance level. The number of Corporation Taxpayers is measured by the number of effective corporation taxpayers. The number of tax inspection is measured by the number of legal products published. The Taxpayer Compliance level is measured from the ratio of the number of Corporation Monthly Tax Return act 25 reported on time with the number of effective corporation taxpayer. The Income Tax revenue is the total revenue of corporation income tax act 25.This study used multiple linier regression with quantitative data that obtained from Tambora Tax Service Office for the period of Januari 2010 untill Juni 2013. This research states that the number of Corporation Taxpayers, Taxpayer compliance level has an influence on the income tax revenue at Tambora Tax Office Service. While the number of tax inspection does not have an influence on the income tax revenue at Tambora Tax Office Service.